Replacement of maize by wheat bran on growth and feed intake pattern in pigs - N. Elanchezhian; K. Ally (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The experiment was conducted to assess the effect of replacement of maize by wheat bran on growth and feed conversion efficiency in Large White Yorkshire (LWY) pigs. Thirty weaned piglets were randomly divided into three groups and were allotted to the three dietary treatments, T1 (control ration as per NRC, 1998), T2 (50 per cent of maize of control ration replaced by wheat bran) and T3 (100 per cent of maize of control ration replaced by wheat bran) and maintained for 70 days. The daily feed intake, fortnightly body weight were recorded and average daily gain and feed conversion efficiency were calculated. The average daily gain and feed conversion efficiency were 813.00, 769.86, 678.43 g and 2.80, 2.88, 3.08, respectively for three dietary treatments. There was no significant difference in the performance between pigs belongs to T1 and T2 treatments but had higher average daily gain and feed conversion efficiency than that of T3 treatment. This study reveals that pigs fed diet with 50 per cent of maize replaced by wheat bran performed in a similar way to that of control fed group and was better than those fed diet with 100 per cent replacement of maize by wheat bran.